Strategic Imperatives of Sustainable Tourism Development in Ukraine - Konarivska, Oksana; Khakhlov, Oleksii (Herald of Economics, 2026)
The growth of tourist flows, increasing anthropogenic pressure, and contemporary transformational challenges, including wartime conditions, necessitate a transition to sustainable tourism development models as a prerequisite for balanced resource use and enhanced resilience of the tourism sector. The purpose of the article is to provide a theoretical substantiation of the strategic imperatives for sustainable tourism development and to develop an assessment toolkit based on the integration of economic, social, environmental, and institutional and governance dimensions. The conceptual content of sustainable tourism is refined, and its core principles are systematized. The most relevant Sustainable Development Goals for the tourism sector are identified, and their role in shaping strategic development priorities is substantiated. An assessment toolkit for sustainable tourism is developed and structured across economic, social, environmental, and institutional and governance dimensions, ensuring a comprehensive coverage of both conditions and outcomes of tourism development. A system of indicators is proposed, with clearly defined data sources and assessment methods, which enhances the practical applicability of the toolkit for monitoring sustainable tourism development. The proposed approach to sustainable tourism assessment provides a methodological basis for informed decision-making and contributes to improving the resilience of tourist destinations. Further research involves the empirical testing of the proposed toolkit at the level of tourist destinations and regions of Ukraine.